Potential application of spectroscopic method for size and shape detection fruits: a review - Mat Lazim, Siti Saripa Rabiah; Mat Nawi, Nazmi (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Size, shape, color and absence of visual defects are among the parameters used to define a quality level of the fruits. In agriculture, size of the products becomes major benchmark by customers to buy vegetables and fruits. This crops physical always related to the product’s quality. The size and shape of agricultural products are most assessed by experienced operators. However, this conventional technique is inconsistent, subjective and time consuming. Numerous studies have been conducted to non-destructively measure the size and shape of agricultural products non-by using machine vision, acoustics and nuclear magnetic resonance (NMR).Lately, spectroscopy has been explored as an interesting alternative method to solve this problem because of its good rapidity, high consistency and suitable for routine analysis. Therefore, this review discusses the potential of spectroscopic method to determine the size of agricultural products.